Clinical experience with SUBA-itraconazole at a tertiary paediatric hospital. (15th September 2020) - Abbotsford, Joanne; Foley, David A; Goff, Zoy; Bowen, Asha C; Blyth, Christopher C; Yeoh, Daniel K
Abstract: Background: Itraconazole remains a first-line antifungal agent for certain fungal infections in children, including allergic bronchopulmonary aspergillosis (ABPA) and sporotrichosis, but poor attainment of therapeutic drug levels is frequently observed with available oral formulations. A formulation of 'SUper BioAvailability itraconazole' (SUBA-itraconazole; Lozanoc ® ) has been developed, with adult studies demonstrating rapid and reliable attainment of therapeutic levels, yet paediatric data are lacking. Objectives: To assess the safety, efficacy and attainment of therapeutic drug levels of the SUBA-itraconazole formulation in children. Methods: A single-centre retrospective cohort study was conducted, including all patients prescribed SUBA-itraconazole from May 2018 to February 2020. The recommended initial treatment dose was 5 mg/kg twice daily (to a maximum of 400 mg/day) rounded to the nearest capsule size and 2.5 mg/kg/day for prophylaxis. Results: Nineteen patients received SUBA-itraconazole and the median age was 12 years. The median dose was 8.5 mg/kg/day and the median duration was 6 weeks. Indications included ABPA (16 patients), sporotrichosis (1), cutaneous fungal infection (1) and prophylaxis (1). Of patients with serum levels measured, almost 60% (10/17) achieved a therapeutic level, 3 with one dose adjustment and 7 following the initial dose. Adherence to dose-adjustment recommendations amongst the seven patients not achieving therapeutic levels was poor. Of patients with ABPA, 13/16 (81%) demonstrated a therapeutic response in IgE level. SUBA-itraconazole was well tolerated with no cessations related to adverse effects. Conclusions: SUBA-itraconazole is well tolerated in children, with rapid attainment of therapeutic levels in the majority of patients, and may represent a superior formulation for children in whom itraconazole is indicated for treatment or prevention of fungal infection.